Energy efficiency in sustainable constructions - Orientation due to sunshine in climates of tropical latitudes - Linares Zaferson, Víctor (2023)
In the process of designing a building, orientation is one of the criteria used in the approach, which depends on several factors, including solar radiation due to sunlight and climate. During the design process, a pre-design stage and a final design stage are carried out in which it is possible to quantify the results of the energy balance. The objective of the research proposes a method to determine the orientation of a building in tropical climates in order to achieve buildings with energy standards close to zero, with greater energy efficiency. The methodology used is inductive, based on the designer's experience, analyzes questions and induces solutions. It uses the "orthogonal projection of the apparent path of the sun" and the ambient temperature conditions. The result obtained from the investigation offers an application procedure, practical and easy to execute, to be used in the first stage of design, which allows to determine a priori the adequate orientation of the walls and windows of a building to achieve the maximum efficiency of the balance energy for a given climate. The procedure is validated through an energy balance calculation for a prototype in the Peruvian territory.